Analysis of Business Implementation through the Blue Ocean Strategy Approach in an Effort to Face Competition in Culinary SMEs - Nisrina, Delima Nurul; Ribhan; Husna, Nurul (Asian Journal of Applied Business and Management, 2024)
The food and beverage industry, a cornerstone of the national economy, is thriving in Bandar Lampung, notably through its rapidly growing MSME sector. Among these, the culinary business, such as Mamikeki Banana Nugget, stands out due to its high growth potential. This study examines the application of Blue Ocean Strategy in Mamikeki Banana Nugget MSMEs to address competition. Using qualitative descriptive methods, the study analyzes data through reduction, strategy canvas, and Blue Ocean strategy index. Findings reveal Mamikeki's success in differentiating from competitors via the Blue Ocean Strategy, though the price dimension remains in the red ocean. To improve, the business should evaluate pricing and enhance communication through taglines to clarify value to buyers.